Organization Theory—Business Success Depends on it - Isaack, Thomas S. (Academy of Management Journal, 1958)
Discusses the significance of organizational theory and formal organization to business success. Statements on the impressions of managers about the significance of organizational theory and formal organization; Dimensions of theory; Principles that composed the framework of organization theory.